2019
DOI: 10.1056/nejmoa1900906
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Prevention of Type 2 Diabetes

Abstract: BACKGROUNDObservational studies support an association between a low blood 25-hydroxyvitamin D level and the risk of type 2 diabetes. However, whether vitamin D supplementation lowers the risk of diabetes is unknown. METHODSWe randomly assigned adults who met at least two of three glycemic criteria for prediabetes (fasting plasma glucose level, 100 to 125 mg per deciliter; plasma glucose level 2 hours after a 75-g oral glucose load, 140 to 199 mg per deciliter; and glycated hemoglobin level, 5.7 to 6.4%) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
401
6
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(440 citation statements)
references
References 28 publications
18
401
6
15
Order By: Relevance
“…Previous studies proposed that RCTs of nutrients such as vitamin D be based on nutrient status, such as 25(OH)D concentration, seeking to enroll participants with low values, supplementing them with enough agent to raise the concentration to values associated with good health, and measuring achieved concentrations as well as cofactors such as vitamin C, omega-3 fatty acids, and magnesium [64,65],. Two recently completed RCTs reported significantly reduced incidence in the secondary analyses for cancer [66] and diabetes mellitus [67]. Table 2.…”
Section: Clinical and Epidemiological Findings Regarding Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies proposed that RCTs of nutrients such as vitamin D be based on nutrient status, such as 25(OH)D concentration, seeking to enroll participants with low values, supplementing them with enough agent to raise the concentration to values associated with good health, and measuring achieved concentrations as well as cofactors such as vitamin C, omega-3 fatty acids, and magnesium [64,65],. Two recently completed RCTs reported significantly reduced incidence in the secondary analyses for cancer [66] and diabetes mellitus [67]. Table 2.…”
Section: Clinical and Epidemiological Findings Regarding Covid-19mentioning
confidence: 99%
“…Clinical Severe cases associated with pneumonia Inverse correlation for CAP [68,69] Increased production of pro-inflammatory cytokines such as IL-6 Inverse correlation [70,71] Increased CRP Inverse correlation [72,73] Increased risk of sepsis Inverse correlation [74,75] Risk of ARDS Inverse correlation [76,77] Risk of heart failure Inverse correlation [78,79] Risk of diabetes mellitus Inverse correlation [67,80] Epidemiological Began in December 2019 in China, spread mainly to northern midlatitude countries Low 25(OH)D values in winter [48,81] Males have higher incidence and much higher CFRs than females Smoking reduces 25(OH)D [82] CFR increases with age Chronic disease rates increase with age; vitamin D plays a role in reducing risk of chronic diseases [83] Higher CFR for diabetics Diabetics may have lower 25(OH)D [84] Higher CFR for diabetics Lower 25(OH)D associated with increased risk of incidence [85] Higher CFR for hypertension Lower 25(OH)D may be associated with increased risk of incidence [86] Higher CFR for cardiovascular disease Lower 25(OH)D associated with increased risk of incidence and death [87] Higher CFR for chronic respiratory disease For COPD patients, 25(OH)D inversely correlated with risk, severity, and exacerbation [88] Found at higher rates in regions with elevated air pollution Air pollution associated with lower 25(OH)D concentrations [89] Note: 25-hydroxyvitamin D ((25(OH)D); acute respiratory distress syndrome (ARDS); community-acquired pneumonia (CAP); case-fatality rate (CFR); interleukin 6 (IL-6); chronic obstructive pulmonary disease (COPD); C-reactive protein (CRP); vitamin D deficiency (VDD). Table 3 lists some findings for vitamin D supplementation in reducing the clinical effects of COVID-19 infection found from treating other diseases.…”
Section: Characteristics Relation To 25(oh)d Referencementioning
confidence: 99%
“…Intervention studies have shown that obese subjects need more vitamin D than normal‐weight subjects to achieve similar serum 25OHD concentrations as based on a comparison between an overview of such studies . However, vitamin D supplementation of vitamin D–replete prediabetic subjects did not decrease their risk of progression to type 2 diabetes . Whether supplementation of more vitamin D–deficient subjects may generate better results is yet unclear.…”
Section: ‐Hydroxylase Activity (Cyp2r1)mentioning
confidence: 99%
“…(5,16) However, vitamin D supplementation of vitamin D-replete prediabetic subjects did not decrease their risk of progression to type 2 diabetes. (24) Whether supplementation of more vitamin D-deficient subjects may generate better results is yet unclear. Now that the dogma of a nonregulated CYP2R1 has been challenged, one may also question other "dogmas" regarding vitamin D metabolism ( Fig.…”
Section: -Hydroxylase Activity (Cyp2r1)mentioning
confidence: 99%
“…The recently reported VitD and Type 2 Diabetes (D2d) Study enrolled more than 2400 prediabetic patients who were given placebo or 4000 IU VitD per day, the upper limit of recommended dose. A total of 99% of participants completed the 2.5‐year follow‐up . After 2.5 years of VitD treatment, the 25(OH)D level of the VitD group reached 52 ng/mL, while that of the placebo group remained at 28 ng/mL.…”
Section: Explorations On the Prevention Effect Of Vitd On Type 2 Diabmentioning
confidence: 99%